2015
DOI: 10.1007/s11934-015-0485-y
|View full text |Cite
|
Sign up to set email alerts
|

Management of Nocturia in the Female

Abstract: Nocturia is a common but overlooked lower urinary tract symptom that substantially reduces patient health and quality of life. Though traditionally viewed as occurring predominantly in males, nocturia has been found to be equally as prevalent in females. The recent emphasis on the importance of nocturia has resulted in a surge of research studies, providing a foundation for current and future management decisions. In this review, we describe the current recommendations for the female patient in light of the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…Nocturia has been found to equally affect men and women [5,6]. However, the pathophysiology of nocturia, and inherently the treatment patterns and outcomes, may differ widely between male and female patients [7,8]. Possibly because nocturia has for a long time been regarded as a prostatic symptom [3,4], the specificities of nocturia in female patients have rarely been studied [7,8].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nocturia has been found to equally affect men and women [5,6]. However, the pathophysiology of nocturia, and inherently the treatment patterns and outcomes, may differ widely between male and female patients [7,8]. Possibly because nocturia has for a long time been regarded as a prostatic symptom [3,4], the specificities of nocturia in female patients have rarely been studied [7,8].…”
Section: Discussionmentioning
confidence: 99%
“…The prostate can play a significant role in men, whilst gender-specific factors may be involved in women, such as hormonal status and dysfunctions, parity, history of gynaecological surgery, etc. [7,8]. As a result, one may assume that therapeutic patterns and response to treatment may differ according to gender for nocturia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One symptom in particular, nocturia, seems to be consistently overlooked in clinical practice with regard to its specific aetiology, impact on quality‐of‐life and treatment, despite its high prevalence . The analysis of 43 trials of community‐dwelling people demonstrated that 20.4%–43.9% of women and 11.0%–35.2% of men aged 20–40 years have nocturia ≥1 times per night and 4.4%–18% of women and 2.0%–16.6% of men report about nocturia ≥2 times per night .…”
Section: Background and Objectivesmentioning
confidence: 99%
“…quality-of-life and treatment, despite its high prevalence. 13 The analysis of 43 trials of community-dwelling people demonstrated that 20.4%-43.9% of women and 11.0%-35.2% of men aged 20-40 years have nocturia ≥1 times per night and 4.4%-18% of women and 2.0%- 16.6% of men report about nocturia ≥2 times per night. 14 The prevalence of nocturia rises dramatically with ageing.…”
mentioning
confidence: 99%